A Survey on Content-Based Video Retrieval Techniques - Maitree, Nagariya; Jaliya, UK; Holia, MS (International Journal of Computer Sciences and Engineering, 2019)
In the recent digital world, the amount of processing of videos is increasing rapidly. For this purpose, video retrieval systems are dominating today’s world. Video retrieval systems include proper analysis of videos for appropriate retrieval. The retrieval of videos can be done based on the text or annotation attached to it. But retrieval based on the content has become more influencing over text-based retrieval as it describes a video in a much better way than described by text. Content-based video retrieval systems analyze the contents of a video such as colour, texture, shape, etc. This system involves many stages with multiple techniques for each one as per the survey done till now. To analyze the different techniques, multiple datasets have been used containing videos of different categories. The best technique applied at each stage for frame extraction, feature extraction, classification and retrieval of videos makes the system more accurate and efficient.